DAMPAK SOSIAL EKONOMI PEMBANGUNAN DI KAWASAN SERIBU RUMAH GADANG BAGI MASYARAKAT NAGARI KOTO BARU KABUPATEN SOLOK SELATAN - Susiyanti Meilina; Roni Russandi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Sungai Pagu, South Solok Regency, became a world cultural heritage to the Organization. The cultural heritage in the area of a thousand rumah gadang is a symbol of tourism in the South Solok area, according to the Acting Regent of South Solok, Drs. H. Abdul Rahman, S.H., M.H. This uniqueness must be used as best as possible to improve the community's economy, and it must be used as best as possible to generate Regional Original Income (PAD) for the region and increase the community's economy while reducing unemployment and creating job opportunities. The objectives of this study are: 1) To determine the socio-economic impact of development in the area of a thousand rumah gadang for the Nagari Koto Baru community, South Solok Regency; 2) To find out what are the inhibiting factors in the socio-economic development in the area of a thousand rumah gadang for the Nagari Koto Baru community, South Solok Regency; 3) To find out what are the efforts made to overcome the socio-economic constraints of development in the area of a thousand rumah gadang for the Nagari Koto Baru community, South Solok Regency. This type of research is qualitative research.